Polyolefin elastomer ionomers and methods related thereto

By ionomizing using sulfonyl azide derivative or potassium hydroxide in the polyolefin elastomer, a functionalized polyolefin elastomer ionomer composition is solved, and the existing polyolefin elastomer lacks elasticity and heat resistance at high temperatures is achieved, and improved elasticity and mechanical properties are achieved.

CN119585319APending Publication Date: 2025-03-07EXXONMOBIL CHEMICAL PATENTS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380054825.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-21
Filing Date
2023-06-16
Publication Date
2025-03-07

Smart Images

  • Figure BDA0005249104730000071
    Figure BDA0005249104730000071
  • Figure BDA0005249104730000171
    Figure BDA0005249104730000171
  • Figure BDA0005249104730000182
    Figure BDA0005249104730000182
Patent Text Reader

Abstract

The present application relates to polyolefin elastomer ionomers and methods related thereto, and more particularly to propylene-based elastomer ionomers and methods of production and uses related thereto. The polyolefin elastomer ionomer includes at least a polyolefin component and a metal-based neutralizer component. The polyolefin elastomer ionomers may exhibit improved elasticity at body temperature or at higher temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 391,092, filed on July 21, 2022, the entire contents of which are incorporated herein by reference. Field of the Invention

[0003] The present application relates to polyolefin elastomeric ionomers and methods related thereto, and more particularly to propylene-based elastomeric ionomers and methods of production and uses related thereto.

[0004] background

[0005] Elastomers (e.g., rubber) and elastomeric layered structures are commonly used in a variety of applications, including consumer products such as disposable hygiene products. These disposable hygiene products may include diapers, training pants, and adult incontinence products and require sufficient elastic properties at room and body temperatures, such as in the waist, ear, side panel, and cuff areas, for effective use.

[0006] Elastomeric structures based on styrene block copolymers (SBCs), such as elastomeric laminate films or elastomeric nonwoven webs, exhibit excellent elastic and thermophysical properties; however, structures based entirely on SBCs are costly and often prohibited for use in consumer products. Lower cost SBCs include, for example, those that are unhydrogenated SBCs (e.g., styrene-isoprene-styrene, styrene-butadiene-styrene, etc.) and hydrogenated mid-block SBCs (e.g., styrene-ethylene / butylene-styrene, styrene-ethylene / propylene-styrene, etc.). However, unhydrogenated SBCs exhibit limited processing windows, which are attributed to poor thermal degradation, processability, and reduced mechanical properties; hydrogenated mid-block SBCs may exhibit relatively greater thermal stability but are expensive to manufacture.

[0007] However, more environmentally and economically friendly elastomers such as polyolefin-based elastomers currently suffer from limited elasticity and heat resistance compared to SBCs, and those current elastomers that meet the elasticity needs of such consumer products can be difficult to handle due to tack and other processability barriers and often require crosslinking to balance properties, especially at body temperature conditions or elevated temperatures.

[0008] Therefore, there is a need for polyolefin-based elastomers that exhibit sufficient elasticity and thermal stability as replacements for SBCs. SUMMARY OF THE INVENTION

[0010] The present application relates to polyolefin elastomeric ionomers and methods related thereto, and more particularly to propylene-based elastomeric ionomers and methods of production and uses related thereto.

[0011] In one or more aspects, the present disclosure provides a functionalized polyolefin elastomer ionomer composition. The composition includes a polyolefin component, at least 0.1 parts by weight of a sulfonyl azide derivative component, and a reaction product of a metal-based neutralizer component containing an elemental metal or metal compound containing at least one of aluminum, calcium, magnesium, sodium, and zinc. The sulfonyl azide derivative component functionalizes the polyolefin component. The sulfonyl azide derivative component includes at least one of an organic anhydride compound or an organic acid compound and is present in an amount per 100 parts by weight of the polyolefin component. The degree of neutralization of one or both of the organic anhydride component or the organic acid component of the sulfonyl azide derivative component is at least 20%.

[0012] In one or more aspects, the present disclosure provides a method of melt mixing a polyolefin component, at least 0.1 parts by weight of a sulfonyl azide derivative component, and a metal-based neutralizer component containing an elemental metal or metal compound containing at least one of aluminum, calcium, magnesium, sodium, and zinc. The sulfonyl azide derivative component functionalizes the polyolefin component. The sulfonyl azide derivative component contains at least one of an organic anhydride compound or an organic acid compound and is present in an amount per 100 parts by weight of the polyolefin component. The degree of neutralization of one or both of the organic anhydride component or the organic acid component of the sulfonyl azide derivative component is at least 20%.

[0013] In one or more aspects, the present disclosure provides a carboxylated propylene elastomeric ionomer composition. The composition includes the reaction product of a polyolefin component grafted with an acid hydride and a metal hydroxide-based neutralizer component containing an elemental metal or metal compound comprising at least one of potassium, sodium, or calcium.

[0014] These and other features and properties and / or uses of the polyolefin elastomeric ionomers disclosed in the present disclosure and their advantageous applications will become apparent from the following detailed description.

[0015] BRIEF DESCRIPTION OF THE DRAWINGS

[0016] To assist one of ordinary skill in the relevant art in making and using the subject matter herein, reference is made to the accompanying drawings. The following drawings are included to illustrate certain aspects of the present disclosure and should not be construed as an exclusive configuration. The disclosed subject matter is capable of significant modifications, alterations, combinations, and equivalences in form and function as will occur to one of ordinary skill in the art having the benefit of the present disclosure.

[0017] Figure 1 SUMMARY OF THE INVENTION A reaction scheme for preparing a representative azidosulfonylbenzoic acid carboxypropylene elastomeric ionomer according to one or more aspects of the present disclosure is shown in FIG.

[0018] Figure 2A and2B Small amplitude oscillatory shear measurements of representative azidosulfonylbenzoic acid carboxypropylene elastomeric ionomers compared to conventional polyolefin elastomers are shown according to one or more aspects of the present disclosure.

[0019] Figure 3 The properties of representative azidosulfonylbenzoic acid carboxypropylene elastomeric ionomers compared to conventional polyolefin elastomers are shown according to one or more aspects of the present disclosure.

[0020] Figure 4 is the differential molecular weight (dWf / dLogM) curve of a commercially available maleic acid grafted propylene-based elastomer.

[0021] Figures 5A to 5C Small amplitude oscillatory shear measurements of representative carboxypropylene elastomeric ionomers grafted with maleic acid and ionomerized by reaction with potassium hydroxide are shown in comparison to conventional maleic acid grafted polyolefin elastomers according to one or more aspects of the present disclosure.

[0022] Figure 6 is a graph showing the tensile strength and elongation properties of a representative carboxypropylene elastomeric ionomer grafted with maleic acid and ionomerized by reaction with potassium hydroxide compared to a conventional maleic acid grafted polyolefin elastomer according to one or more aspects of the present disclosure.

[0023] Figures 7A to 7D Dynamic mechanical thermal analysis measurements of representative carboxypropylene elastomeric ionomers grafted with maleic acid and ionomerized by reaction with potassium hydroxide are shown in comparison to conventional maleic acid grafted polyolefin elastomers according to one or more aspects of the present disclosure.

[0024] Figure 8 Fourier Transform Infrared Spectroscopy measurements of representative carboxypropylene elastomeric ionomers grafted with maleic acid and ionomerized by reaction with potassium hydroxide compared to conventional maleic acid grafted polyolefin elastomers according to one or more aspects of the present disclosure.

[0025] Fig. 9 is a graph showing compression set data for a representative carboxypropylene elastomeric ionomer grafted with maleic acid and ionomerized by reaction with potassium hydroxide, in accordance with one or more aspects of the present disclosure, compared to a conventional maleic acid grafted polyolefin elastomer.

[0026] Fig. 10A and 10B

[0046] Shown are tensile strength (stress) data for representative carboxypropylene elastomeric ionomers grafted with maleic acid and ionomerized by reaction with potassium hydroxide in comparison to conventional maleic acid grafted polyolefin elastomers according to one or more aspects of the present disclosure.

[0027] Fig.11A and 11B Elastic recovery data for a representative carboxypropylene elastomeric ionomer grafted with maleic acid and ionomerized by reaction with potassium hydroxide is shown in accordance with one or more aspects of the present disclosure, compared to a conventional maleic acid grafted polyolefin elastomer.

[0028] Details

[0029] The present application relates to polyolefin elastomeric ionomers and methods related thereto, and more particularly to propylene-based elastomeric ionomers and methods of production and uses related thereto.

[0030] The polyolefin-based elastomeric ionomers obtained by one or more reactions of the present disclosure exhibit relatively improved elastic properties at room temperature, body temperature conditions and elevated temperatures, as well as improved mechanical and structural properties. These polyolefin-based elastomeric ionomers are suitable for replacing SBCs for consumer disposable sanitary products or as a substitute for SBCs for consumer disposable sanitary products, which, for example, suffer from poor processability and manufacturability (e.g., exhibit adhesion to rollers or other machinery, etc.), require relatively high CO2 input and are costly. Polyolefin-based elastomeric ionomers are also suitable for replacing traditional propylene-based elastomers, which often lack suitable elasticity and high melt strength, resulting in processability issues such as foaming, high-speed sheet extrusion, thermoforming, etc. Although high melt strength can be solved by adding long chain branches to linear polymer structures, the polymer network often becomes rigid and affects elasticity, or is not suitable for certain conversion technologies.

[0031] Typical ionomerization uses complex sulfonation procedures or peroxide maleic anhydride grafting, neither of which addresses body temperature elasticity, processability, manufacturability, or adhesion. The present disclosure provides ionomerization using sulfonyl azide derivatives or potassium hydroxide to address these issues.

[0032] Definition and test methods

[0033] As used herein, "wt%" means percent by weight, "volume%" means percent by volume, "parts" means parts by weight, and all molecular weights such as Mw and Mn are in grams per mole (g / mol) unless otherwise indicated.

[0034] The term "polymer" and their grammatical variations refer to any carbon-containing compound having repeating units derived from one or more different monomers and includes homopolymers, copolymers, terpolymers, etc. A "copolymer" is a polymer having two or more monomer units that are different from each other.

[0035] As used herein, when a polymer is referred to as comprising a monomer, the monomer is present in the polymer in the polymerized form of the monomer or in the form of a derivative of the monomer. The term "derived unit" as used herein refers to the polymerized form of the monomer from which the polymer is derived. For example, when a copolymer is said to have an "ethylene" content of 35% to 55% by weight, it is understood that the monomer units in the copolymer are derived from ethylene in the polymerization reaction and the derived units are present at 35% to 55% by weight based on the weight of the copolymer.

[0036] As used herein, "elastomer" or "elastomeric composition" and their grammatical variations refer to any polymer or composition of polymers (e.g., blends of polymers) that conform to the definition of ASTM D1566-21 (2021). Elastomers include mixed blends of polymers, such as melt blends and / or reactor blends of polymers. The term may be used interchangeably with the term "rubber(s)".

[0037] As used herein, the term "ionomer" and their grammatical variants refer to polymers containing ionic groups that are stabilized by crosslinks. According to various aspects of the present disclosure, in order to obtain an ionomer having the desired properties of a fully crosslinked polymer, for example, the ionomer should carry an average of more than two ionic groups per molecule (a molar functionality greater than 2). The resulting fully crosslinked ionomer can be obtained by neutralizing a polymer carrying an average of slightly more than two functional groups (e.g., carboxyl groups, sulfonic acid groups, etc., and any combination thereof) to a degree of neutralization of at least 20% and preferably up to 200%. Alternatively, an ionomer with similar properties can be achieved using a functionalized polymer having a molar functionality significantly greater than 2 and neutralized to such an extent ("neutralization") to provide a polymer having an average of slightly more than two ionic groups / molecule.

[0038] As used herein, the term "neutralization degree" and their grammatical variations refer to the number of metal equivalents of the metal-based neutralizing agent used per equivalent of carboxyl groups multiplied by 100%. Thus, when the degree of neutralization exceeds 100%, it indicates the presence of excess neutralizing agent, which would also be present in a thermoplastic elastomer composition based on such a carboxylated elastomer and thus have a degree of neutralization greater than 100%.

[0039] The Shore A hardness was measured using a durometer according to ASTM D2240-15 (2021).

[0040] On injection molded panels according to ASTM D412-16 (2021) by using INSTRON TM A testing machine (MA, USA) was used to measure tensile strength, modulus at 100% elongation ("M100") and ultimate elongation.

[0041] Tensile set (Method 1) is measured at 70°C and by applying 25% strain for 22 h. The sample is removed under tension and allowed to cool. The measurement is performed for 30 min using a crosshead speed of 100 millimeters per minute (mm / min) after releasing the tension.

[0042] Tensile set (Method 2) is measured at 70°C and by applying 100% strain for 22 h. The sample is removed under tension and allowed to cool. The measurement is performed for 30 min using a crosshead speed of 100 millimeters per minute (mm / min) after releasing the tension.

[0043] Tensile set (Method 3) is measured at room temperature (RT) by applying 100% strain for 10 min. The sample is removed under tension and allowed to cool. The measurement is performed for 10 min using a crosshead speed of 100 millimeters per minute (mm / min) after releasing the tension.

[0044] Tensile set (Method 4?) was measured at 37°C by applying 100% strain for 10 min. The sample was removed under tension and allowed to cool. The measurement was performed for 10 min using a crosshead speed of 100 millimeters per minute (mm / min) after releasing the tension.

[0045] Elastic recovery was measured according to ASTM D6084-21 (2021) using an RSA rheometer (TA INSTRUMENTS, DE, USA) with a tensile fixture and a deformation rate of 1 millimeter / second (mm / s).

[0046] Dynamic mechanical thermal analysis (DMTA) was measured according to ASTM E1867-18 (2018) using an RSA rheometer (TA INSTRUMENTS, DE, USA) at a frequency of 1 Hertz (Hz) and a strain of 0.1%.

[0047] The specific heat was determined by differential scanning calorimetry (DSC) according to ASTM E1269-11 (2018) using a heating and cooling rate of 10°C / minute (°C / min).

[0048] Using NICOLET TM Fourier transform infrared spectroscopy (FTIR) was performed using an iS50 FT-IR spectrometer (THERMO FISHER SCIENTIFIC, Massachusetts, USA) using the following transmission mode: 4 cm -1 Resolution, scan speed of 0.2 cm / s and scan number 32.

[0049] The compression set is measured at 70°C and by applying a 25% deformation for 22 hours. The sample is removed under compression and allowed to cool under compression. The measurement is made after release from compression.

[0050] Molecular weight distribution (MWD), comonomer content, LCB were measured using gel permeation chromatography equipped with an IR5 infrared detector GPC-4D (POLYMER CHAR, Valencia, Spain).

[0051] Rheological properties were measured by small amplitude oscillatory shear (SAOS) measurements. SAOS measurements were performed on an ARES-G2 rheometer (TA Instruments, Delaware, USA) at elevated temperatures under nitrogen atmosphere. The dynamic properties of the ionomers were characterized in the frequency range of 0.1 rad / s-256 rad / s (logarithmic scale).

[0052] Sulfonyl Azide Derivative (SAD) Carboxyl Polyolefin Elastomer Ionomer

[0053] In one or more aspects of the present disclosure, a carboxyl polyolefin elastomeric ionomer is provided which is ionomerized by reaction with a sulfonyl azide derivative (SAD). The polyolefin elastomeric ionomer is at least partially neutralized and acid functionalized, as described herein. More particularly, the polyolefin-based elastomeric ionomer of the present disclosure can be formed by the reaction of a polyolefin component, a SAD component, and a metal-based neutralizer component. The SAD component comprises an organic anhydride or an organic acid and can be present in an amount greater than at least 0.1 parts by weight of the polyolefin component, including up to 10 parts by weight of the polyolefin component, including any values ​​and subsets therebetween. The degree of neutralization by using a metal-based neutralizer component can be at least 20%, including up to 200%, including any values ​​and subsets therebetween.

[0054] Examples of suitable SADs with organic acids may include, but are not limited to, 3-azidosulfonylbenzoic acid, 4-azidosulfonylbenzoic acid, 4-carboxylbenzenesulfonylazide (CBSA), 4-azidosulfonyl-phthalic acid and 4-azidosulfonyl-phenoxyacetic acid, and such acids with additional substituents attached to the aromatic core, such as, but not limited to, 2-chloro-5-azidosulfonylbenzoic acid, 4-neopentyl-5-azidosulfonylbenzoic acid, 4-ethyl-5-azidosulfonylbenzoic acid and 2-hydroxy-5-azidosulfonylbenzoic acid. Preferred SAD acids are 4-azidosulfonylbenzoic acid and / or 4-carboxylbenzenesulfonylazide (CBSA). Any SAD acid may be used in combination without departing from the scope of the present disclosure.

[0055] Examples of suitable SADs with organic anhydrides may include, but are not limited to, 5-(azidosulfonyl)endo-cis-bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, 3-(2,5-dioxotetrahydrofuran-3-yl)-2-methylpropane-1-sulfonyl azide, and the like, and any combination thereof. Another suitable SAD with organic anhydrides used alone or in combination is represented by the following chemical structure 1:

[0056]

[0057] Where R 1 , R 2 and R 3 Each is H- or an alkyl group.

[0058] Examples of suitable polyolefins include, but are not limited to, propylene-ethylene copolymers, polyethylene, polyolefins, and the like, and any combination thereof.

[0059] Any SAD acid or SAD anhydride may be used in combination without departing from the scope of the present disclosure.

[0060] In principle any neutralizing agent may be used, but metal-based neutralizing agents are preferred. Examples of such metal-based neutralizing agents include oxide-, hydroxide-, salt-, and alcoholate-type neutralizing agents, including, for example, magnesium hydroxide and zinc oxide. When the neutralizing agent is a salt-type neutralizing agent, the salt is preferably based on an acid having an acid strength (pKa) greater than the acid strength of the carboxyl groups present in the carboxylated elastomer. Metal oxide-type neutralizing agents are most preferred, with zinc oxide (ZnO) being a preferred metal oxide-type neutralizing agent.

[0061] In general, the degree of neutralization of the carboxyl groups will be at least about 20% and up to 200%, including any values ​​and subsets therebetween. That is, a fully cross-linked polymer can be used to obtain the highest degree of coherence (as demonstrated by low flow and high tensile strength at elevated temperatures) for a given carboxylated polymer, thus having a degree of neutralization of 100%. However, it has surprisingly been found that a degree of neutralization exceeding 100% can have a beneficial effect on the tensile properties of the compositions of the elastomeric ionomers described herein. Therefore, it is preferred to use a carboxylated elastomeric polymer having a degree of neutralization of at least 200%.

[0062] In one or more aspects of the present disclosure, it is desirable that the compositions described herein exhibit a degree of thermoplasticity. In general, the neutralized SAD carboxyl polyolefin elastomer ionomers of the present disclosure, particularly those approaching 100% neutralization, will exhibit very little or no flow at elevated temperatures, and will require mixing of plasticizing compounds in order to achieve a sufficient degree of thermoplasticity. Zinc carboxylates have been found to be suitable plasticizers. Although any zinc carboxylates may be used, the carboxylic acid upon which the zinc carboxylates are based is preferably a linear or branched monocarboxylic acid having at least 12 carbon atoms / molecule. Most preferably, the linear monocarboxylic acid is a fatty acid, wherein stearic acid is a preferred fatty acid. Preferred zinc carboxylates are zinc stearate. For every 100 pbw of polymer, the amount of plasticizer is preferably at least 6 parts by weight (pbw) of plasticizer. Most preferably, the weight ratio is in the range of about 10:100 to about 50:100, including any value and subset therebetween.

[0063] The zinc carboxylates employed in the present invention may also be prepared in situ by mixing the corresponding carboxylic acid having at least 12 carbon atoms in its molecule and an amount of a neutralizing agent, preferably at least sufficient to neutralize the carboxyl groups of the carboxylated elastomer and the carboxyl groups of the carboxylic acid.

[0064] Examples of suitable metal-based neutralizing agents include, but are not limited to, elemental metals or metal compounds comprising aluminum, calcium, potassium, magnesium, sodium, zinc, etc., and any combination thereof. For example, the metal compound may include hydroxides or oxides comprising aluminum, calcium, potassium, magnesium, sodium, zinc, etc., and any combination thereof. In a preferred embodiment, when the metal-based neutralizing agent is a hydroxide or oxide, the metal moiety is potassium, sodium, zinc, calcium, or aluminum. As an additional example, the metal-based neutralizing agent may include a carboxylated copolymer of a calcium carboxylate or a zinc carboxylate based on an acid compound selected from linear and branched monocarboxylic acids having at least 12 carbon atoms / molecule.

[0065] In some cases, the SAD carboxyl polyolefin elastomer ionomer is mechanically melt mixed (e.g., using a reactor or extruder) at a temperature in the range of about 100° C. to about 200° C. in the absence of a free radical initiator. The SAD carboxyl polyolefin elastomer ionomer thus produced exhibits excellent elastic properties at body temperature as well as at room temperature. In addition, the SAD carboxyl polyolefin elastomer ionomer exhibits good high temperature processability as measured by small amplitude oscillatory shear.

[0066] In certain specific aspects, one or more representative SAD carboxy polyolefin elastomeric ionomers can be azidosulfonylbenzoic acid (ABA) elastomeric ionomers prepared by reaction with 4-carboxybenzenesulfonamide (CBSA) and subsequent neutralization of the carboxylic acid with a Zn salt such as zinc oxide (ZnO) and / or zinc stearate (ZnSt). Figure 1Shown is a reaction scheme for preparing a representative ABA propylene elastomer ionomer.

[0067] The SAD carboxy polyolefin elastomeric ionomers prepared as described herein can have a Shore A hardness in the range of about 50 to about 80, including any values ​​and subsets therebetween, such as about 50 to about 60, or about 60 to about 70, or about 70 to about 80.

[0068] The SAD carboxy polyolefin elastomeric ionomer may have a 100% modulus in the range of about 1 megapascal (MPa) to about 2 MPa, including any values ​​and subsets therebetween, such as about 1 MPa to about 1.5 MPa, or about 1.5 MPa to about 2 MPa.

[0069] The SAD carboxy polyolefin elastomeric ionomer may have a tensile strength of about 5 MPa to about 20 MPa, including any values ​​and subsets therebetween, such as about 5 MPa to about 15 MPa, or about 10 MPa to about 15 MPa, or about 10 MPa to about 12 MPa, or about 12 MPa to about 15 MPa.

[0070] The SAD carboxy polyolefin elastomeric ionomer can have an ultimate elongation of about 400% to about 950%, including any values ​​and subsets therebetween, for example, about 400% to about 500%, or about 500% to about 600%, or about 600% to about 700%, or about 700% to about 750%, or about 750% to about 800%, or about 800% to about 850%, or about 850% to about 900%, or about 900% to about 950%.

[0071] The SAD carboxy polyolefin elastomeric ionomer can have a 25% elongation at break when released after 22 hours and 70°C for 30 min of about 20% to about 30%, including any values ​​and subsets therebetween, such as about 20% to about 25% or about 25% to about 30%.

[0072] The SAD carboxy polyolefin elastomeric ionomer can have a 50% elongation at break when released after 22 hours and 70°C for 30 min of about 40% to about 60%, including any values ​​and subsets therebetween, such as about 40% to about 50% or about 50% to about 60%.

[0073] The SAD carboxy polyolefin elastomeric ionomer can have a 100% elongation at break when released after 10 minutes and at room temperature of about 1% to about 8%, including any values ​​and subsets therebetween, such as about 1% to about 5%, or about 5% to about 10%, or about 2% to about 4%, or about 6% to about 8%.

[0074] The SAD carboxy polyolefin elastomeric ionomer can have a 100% elongation at break when released after 10 minutes and 37°C of about 3% to about 25%, including any values ​​and subsets therebetween, such as about 3% to about 20%, or about 5% to about 10%, or about 10% to about 25%, or about 15% to about 25%.

[0075] The SAD carboxyl polyolefin elastomeric ionomer may have a relative humidity of about 1000 Pa as measured by SAOS at 190° C. in an angular frequency range of 0.1 rad / s to 100 rad / s. . s to about 100,000Pa . Complex viscosity in the range of s, including any values ​​and subsets therebetween, e.g. about 1000 Pa . s to about 10,000Pa . s, or about 10,000Pa . s to about 25,000Pa . s, or about 25,000Pa . s to about 50,000Pa . s, or about 50,000Pa . s to about 75,000Pa . s, or about 75,000Pa . s to about 100,000Pa . s.

[0076] The SAD carboxy polyolefin elastomeric ionomer may have a relative humidity of about 2.0E+04 Pa as measured by SAOS at 190°C. . s to about 4.0E+04Pa . s, including any values ​​and subsets therebetween, such as about 2.5E+04 Pa . s to about 3.5E+04Pa . s, or about 2.5E+04Pa . s to about 3.0E+04Pa . s.

[0077] The SAD carboxy polyolefin elastomeric ionomer can have a complex modulus (G*) in the range of about 10 MPa to about 100 MPa, including any values ​​and subsets therebetween, such as about 10 MPa to about 25 MPa, or about 25 MPa to about 50 MPa, or about 50 MPa to about 75 MPa, or about 75 MPa to about 100 MPa, as measured by SAOS at 190°C within a phase angle of 0° to 100°.

[0078] The SAD carboxylated polyolefin elastomeric ionomer can have a propylene-ethylene polymer content in the range of about 80 wt % to about 98 wt %, including any values ​​and subsets therebetween, such as about 80 wt % to about 85 wt %, or about 85 wt % to about 90 wt %, or about 90 wt % to about 95 wt %, or about 95 wt % to about 98 wt %. An example of a suitable propylene-ethylene polymer is a polymer having an ethylene content of about 16 wt %, a density of about 0.86 g / cm3 (g / cm 3 ), EXXONMOBIL VISTAMAXX having a melt flow rate (MFR) (230°C, 2.16 kilograms (kg)) of about 3 g / 10 min, a heat of fusion of about 29 joules / gram (J / g), and a melting point of about 56°C to 62°C TM 6100 (Texas, USA).

[0079] The SAD carboxy polyolefin elastomeric ionomer can have a CBSA content in the range of about 0.1 wt % to about 10 wt %, including any values ​​and subsets therebetween, for example, about 0.1 wt % to about 1 wt %, or about 1 wt % to about 2.5 wt %, or about 2.5 wt % to about 5 wt %, or about 5 wt % to about 7.5 wt %, or about 7.5 wt % to about 10 wt %.

[0080] The SAD carboxy polyolefin elastomeric ionomer can have a ZnO content in the range of about 0.1 wt % to about 10 wt %, including any values ​​and subsets therebetween, for example, about 0.1 wt % to about 1 wt %, or about 1 wt % to about 2.5 wt %, or about 2.5 wt % to about 5 wt %, or about 5 wt % to about 7.5 wt %, or about 7.5 wt % to about 10 wt %.

[0081] The SAD carboxy polyolefin elastomeric ionomer can have a ZnSt content in the range of about 0.1 wt % to about 20 wt %, including any values ​​and subsets therebetween, for example, about 0.1 wt % to about 1 wt %, or about 1 wt % to about 5 wt %, or about 5 wt % to about 10 wt %, or about 10 wt % to about 15 wt %, or about 15 wt % to about 20 wt %.

[0082] In one or more aspects, the SAD carboxy polyolefin elastomeric ionomer can have a ZnO content in the range of about 0.1 wt % to about 10 wt %, including any values ​​and subsets therebetween, in combination with a ZnSt content in the range of about 0.1 wt % to about 20 wt %, including any values ​​and subsets therebetween.

[0083] Potassium hydroxide carboxylated propylene elastomer ionomer

[0084] In one or more aspects of the present disclosure, carboxypropylene elastomeric ionomers grafted with maleic acid and ionomerized by reaction with potassium hydroxide (KOH) are provided. It should be appreciated that while the following description is with reference to maleic acid, other anhydrides such as succinic anhydride and other metal hydroxides such as those containing calcium and / or sodium may be substituted without departing from the scope of the present disclosure.

[0085] The KOH propylene elastomeric ionomers show higher melt viscosity and modulus at low angular frequency ranges compared to the control maleic elastomers, which indicates higher melt strength. Indeed, the tensile stress and elongation of the KOH propylene elastomeric ionomers as measured at 190°C indicate improved melt strength resulting from KOH ionomerization.

[0086] At a temperature in the range of about 100°C to about 200°C in the absence of a free radical initiator in a BRABENDER TM The KOH propylene elastomer ionomer was mechanically melt mixed in a mixer at 60 revolutions per minute (rpm) until the torque stabilized. The KOH propylene elastomer ionomer thus produced exhibited excellent elastic properties at high temperatures. In addition, the KOH propylene elastomer ionomer exhibited good high temperature processability, as measured by small amplitude oscillatory shear.

[0087] The KOH propylene elastomeric ionomer is prepared by reacting a propylene-based elastomer grafted with maleic acid and KOH. Alternatively, succinic acid may be used to graft the propylene-based elastomer described herein without departing from the scope of the present disclosure.

[0088] The KOH propylene elastomeric ionomer may have a tensile strength at 190°C of about 5 MPa to about 500 MPa, including any values ​​and subsets therebetween, such as about 5 MPa to about 100 MPa, or about 100 MPa to about 250 MPa, or about 250 MPa to about 500 MPa.

[0089] The KOH propylene elastomeric ionomer can have an ultimate elongation at 190°C of about 150% to about 700%, including any values ​​and subsets therebetween, such as about 150% to about 300%, or about 300% to about 450%, or about 450% to about 600%, or about 600% to about 700%.

[0090] The KOH propylene elastomeric ionomer may have a thermal conductivity of about 500 Pa as measured by SAOS at 190° C. in an angular frequency range of 0.1 rad / s to 100 rad / s. . s to about 1,000,000Pa . s, including any values ​​and subsets therebetween, e.g. about 500 Pa. s to about 200,000Pa . s, or about 200,000Pa . s to about 400,000Pa . s, or about 400,000Pa . s to about 600,000Pa . s, or about 600,000Pa . s to about 800,000Pa . s, or about 800,000Pa . s to about 1,000,000Pa . s.

[0091] The KOH propylene elastomeric ionomer may have a relative humidity of about 1.0E+04 Pa as measured by DMTA within a temperature range of -50°C to 200°C. . s to about 1.0E+08Pa . Complex viscosity in the range of s, including any values ​​and subsets therebetween, such as about 1.0E+04Pa . s to about 1.0E+05Pa . s, or about 1.0E+05Pa . s to about 1.0E+06Pa . s, or about 1.0E+06Pa . s to about 1.0E+07Pa . s, or about 1.0E+07Pa . s to about 1.0E+08Pa . s.

[0092] The KOH propylene elastomeric ionomer can have a storage modulus as measured by SAOS at 190°C in an angular frequency of 0.1 rad / s to 100 rad / s in the range of about 10 MPa to about 100,000 MPa, including any values ​​and subsets therebetween, for example, about 10 MPa to about 1,000 MPa, or about 1,000 MPa to about 25,000 MPa, or about 25,000 MPa to about 50,000 MPa, or about 50,000 MPa to about 75,000 MPa, or about 75,000 MPa to about 100,000 MPa.

[0093] The KOH propylene elastomeric ionomer can have a storage modulus of 1.0E+04 MPa to about 1.0E+09 MPa as measured by DMTA over a temperature range of -50°C to 200°C, including any values ​​and subsets therebetween, for example, from about 1.0E+04 MPa to about 1.0E+05 MPa, or from about 1.0E+05 MPa to about 1.0E+06 MPa, or from about 1.0E+06 MPa to about 1.0E+07 MPa, or from about 1.0E+07 MPa to about 1.0E+08 MPa, or from about 1.0E+08 MPa to about 1.0E+09 MPa.

[0094] The KOH propylene elastomeric ionomer can have a loss modulus in the range of about 10 MPa to about 100,000 MPa, including any values ​​and subsets therebetween, such as about 10 MPa to about 1,000 MPa, or about 1,000 MPa to about 25,000 MPa, or about 25,000 MPa to about 50,000 MPa, or about 50,000 MPa to about 75,000 MPa, or about 75,000 MPa to about 100,000 MPa, as measured by SAOS at 190°C in an angular frequency of 0.1 rad / s to 100 rad / s.

[0095] The KOH propylene elastomeric ionomer can have a loss modulus of 1.0E+04 MPa to about 1.0E+08 MPa as measured by DMTA over a temperature range of -50°C to 200°C, including any values ​​and subsets therebetween, for example, from about 1.0E+04 MPa to about 1.0E+05 MPa, or from about 1.0E+05 MPa to about 1.0E+06 MPa, or from about 1.0E+06 MPa to about 1.0E+07 MPa, or from about 1.0E+07 MPa to about 1.0E+08 MPa.

[0096] As measured by DMTA, tan δ represents damping, i.e., the dissipation of energy in a material under cyclic loading, and is determined by the ratio of the loss modulus to the storage modulus. The KOH propylene elastomeric ionomer may have a tan δ of 0.15 to about 50 as measured by DMTA within a temperature range of -50°C to 200°C, including any values ​​and subsets therebetween, such as from about 0.5 to about 10, or from about 10 to about 25, or from about 25 to about 50.

[0097] The KOH propylene elastomeric ionomer may have a melting temperature (T ) of about 110° C. to about 170° C., or about 140° C. to about 168° C., or about 160° C. to about 165° C. m ), including any values ​​and subsets therebetween. In one or more aspects, they may have a crystallization temperature (Tc) of at least about 60°C, or at least about 80°C, or at least about 70°C, or at least 75°C.c ).

[0098] The KOH propylene elastomeric ionomers can be semi-crystalline polymers. The crystallinity (ΔH) can be determined by dividing the heat of fusion of the sample by the heat of fusion of a 100% crystalline polymer, which is assumed to be 209 Joules / gram (J / g). These KOH propylene elastomeric ionomers can be characterized by a crystallinity of about 5 J / g to about 20 J / g, including any values ​​and subsets therebetween, or at least about 6 J / g, or at least J / g, or in the range of about 6 J / g to about 8 J / g.

[0099] The KOH propylene elastomeric ionomer may have a tensile strength of about 10 MPa to about 15 MPa, including any values ​​and subsets therebetween, such as 10 MPa to about 12 MPa, or about 12 MPa to about 15 MPa.

[0100] The KOH propylene elastomeric ionomer may have an ultimate elongation of about 900% to about 1,200%, including any values ​​and subsets therebetween, such as about 900% to about 1,000%, or about 1,000% to about 1,100%, or about 1,100% to about 1,200%.

[0101] The KOH propylene olefin elastomeric ionomer may have a maleic acid grafted propylene-ethylene polymer content in the range of about 90 wt % to about 99.5 wt %, including any values ​​and subsets therebetween, such as about 90 wt % to about 95 wt %, or about 95 wt % to about 99.5 wt %. An example of a suitable maleic acid grafted propylene-ethylene polymer is ACTI-TECH TM 16MA13 (California, USA), which has an MFR of about 10 g / 10 min (230° C., 2.16 kilograms (kg)) and a grafting level of 0.5%. Another example of a suitable maleic acid grafted propylene-ethylene polymer is EXXONMOBILE VISTAMAXX TM V350 (Texas, USA), which has an MFR of about 50 g / 10 min (230° C., 2.16 kilograms (kg)) and a grafting level of 1.0% or more.

[0102] The KOH propylene elastomeric ionomer can have a KOH content in the range of about 0.5 wt % to about 10 wt %, including any values ​​and subsets therebetween, such as about 0.5 wt % to about 1 wt %, or about 2.5 wt % to about 5 wt %, or about 5 wt % to about 7.5 wt %, or about 7.5 wt % to about 10 wt %. In some cases, the KOH content is 0.5 wt % or 1 wt %.

[0103] Unless otherwise indicated, all numerical values ​​used in this specification and the associated claims expressing the amounts of ingredients, properties such as molecular weight, reaction conditions, etc., should be understood as being modified in all instances by the term "about". Therefore, unless indicated to the contrary, the numerical parameters listed in the following specification and the appended claims are approximate values, which may vary depending on the desired properties sought to be obtained by the embodiment of the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0104] One or more illustrative embodiments including one or more inventive elements are proposed herein. For the sake of clarity, all features of physical implementation are not described or shown in this application. It should be understood that in the development of physical implementations including one or more elements of the present invention, in order to achieve the developer's goal, many specific decisions must be made to achieve, for example, system-related, business-related, government-related and other constraints are observed, which change from time to time with the implementation. Although the developer's efforts may be time-consuming, such efforts are routine tasks for those of ordinary skill in the art who benefit from the present disclosure.

[0105] Although compositions and methods are described herein in terms of "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.

[0106] Implementation

[0107] Embodiments of the present disclosure include:

[0108] Embodiment A: A functionalized polyolefin elastomer ionomer composition comprising: the reaction product of: a polyolefin component; at least 0.1 parts by weight of a sulfonyl azide derivative component, the sulfonyl azide derivative component functionalizing the polyolefin component, wherein the sulfonyl azide derivative component comprises at least one of an organic anhydride compound or an organic acid compound, and wherein the sulfonyl azide derivative component is present in an amount per 100 parts by weight of the polyolefin component; and a metal-based neutralizer component comprising an elemental metal or a metal compound comprising at least one of aluminum, calcium, magnesium, sodium, and zinc, wherein the degree of neutralization of one or both of the organic anhydride component or the organic acid component of the sulfonyl azide derivative component is at least 20%.

[0109] Embodiment B: The method comprises: melt mixing: a polyolefin component; at least 0.1 parts by weight of a sulfonyl azide derivative component, the sulfonyl azide derivative component functionalizing the polyolefin component, wherein the sulfonyl azide derivative component comprises at least one of an organic anhydride compound or an organic acid compound, and wherein the sulfonyl azide derivative component is present in an amount per 100 parts by weight of the polyolefin component; and a metal-based neutralizer component containing an elemental metal or a metal compound comprising at least one of aluminum, calcium, magnesium, sodium and zinc, wherein the degree of neutralization of one or both of the organic anhydride component or the organic acid component of the sulfonyl azide derivative component is at least 20%.

[0110] Non-limiting example embodiments A and B may include one or more of the following elements:

[0111] Element 1: wherein the polyolefin component is a propylene-ethylene copolymer.

[0112] Element 2: The sulfonyl azide derivative component is selected from 4-carboxybenzenesulfonyl azide (CBSA), 3-azidosulfonylbenzoic acid, 5-(azidosulfonyl)endo-cis-bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, 3-(2,5-dioxotetrahydrofuran-3-yl)-2-methylpropane-1-sulfonyl azide, and any combination thereof.

[0113] Element 3: wherein the metal-based neutralizer compound is a carboxylated copolymer of a calcium carboxylate or a zinc carboxylate based on an acid compound selected from linear and branched monocarboxylic acids having at least 12 carbon atoms per molecule.

[0114] Element 4: wherein the metal-based neutralizer compound is a zinc carboxylate based on a linear monocarboxylic fatty acid having at least 12 carbon atoms per molecule.

[0115] Element 5: wherein the metal-based neutralizing agent is a metal hydroxide or a metal oxide of at least one of aluminum, calcium, magnesium, sodium and zinc.

[0116] Element 6: wherein the metal-based neutralizing agent is calcium stearate or zinc stearate.

[0117] Element 7: wherein a reactor or an extruder is used to carry out melt mixing.

[0118] Element 8: wherein the melt mixing is carried out at a temperature of about 100°C to about 200°C.

[0119] By way of non-limiting example, exemplary combinations that may be applied to A include, but are not limited to, 1 and 2, 1 and 3, 1 and 4, 1 and 5, 1 and 6, 2 and 3, 2 and 4, 2 and 5, 2 and 6, 3 and 4, 3 and 5, 3 and 6, 4 and 5, 4 and 6, and any combination of 1, 2, 3, 4, 5 and 6, without limitation.

[0120] By way of non-limiting example, exemplary combinations that may be applied to B include, but are not limited to, 1 and 2, 1 and 3, 1 and 4, 1 and 5, 1 and 6, 1 and 7, 1 and 8, 2 and 3, 2 and 4, 2 and 5, 2 and 6, 2 and 7, 2 and 8, 3 and 4, 3 and 5, 3 and 6, 3 and 7, 3 and 8, 4 and 5, 4 and 6, 4 and 7, 4 and 8, 5 and 6, 5 and 7, 5 and 8, 6 and 7, 6 and 8, 7 and 8, and any combination of 1, 2, 3, 4, 5, 6, 7 and 8, without limitation.

[0121] Embodiment C: A carboxylated propylene elastomeric ionomer composition comprising: the reaction product of: a polyolefin component grafted with an anhydride; and a metal hydroxide based neutralizer component comprising an elemental metal or metal compound comprising at least one of potassium, sodium, or calcium.

[0122] Non-limiting example embodiment C may include one or more of the following elements:

[0123] Element 9: wherein the acid anhydride is maleic anhydride or succinic anhydride.

[0124] Element 10: wherein the metal hydroxide based neutralizing agent is potassium hydroxide.

[0125] Element 11: wherein the polyolefin component is a propylene-ethylene copolymer.

[0126] By way of non-limiting example, exemplary combinations applicable to C include, but are not limited to, 9 and 10, 9 and 11, 10 and 11, and any combination of 9, 10 and 11, without limitation.

[0127] In order to facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should in no way be construed as limiting or defining the scope of the present invention. Example

[0128] Example 1. In this example, two experimental ABA propylene elastomer ionomers were prepared in accordance with the present disclosure and using EXXONMOBIL VISTAMAXX TM 6100 (without RCP) (VMX6100), CBSA (SIGMA ALDRICH, CAS#17202-49-2, Missouri, USA), ZnO and ZnSt. The experimental ionomers are labeled IEx1 and 1Ex2 and are prepared according to the composition of Table 1.

[0129] Table 1

[0130]

[0131]

[0132] use The experimental samples were melted (flux) in a mixer (Duisburg, Germany) and mixed at 190°C. VMX6100 was added to the mixing tank and allowed to melt for 3 min or until the torque stabilized. CBSA powder was then added and allowed to react with the polymer for 3 min, after which ZnO and ZnSt were added to convert the grafted carboxylic acid into an ionic salt. Finally, IRGANOX TM 1010 (BASF, Ludwigshafen, Germany) was used as a stabilizer.

[0133] The properties of IEx1 and IEx2 were compared with VMX6100 as a control. The results are provided in Table 2.

[0134] Table 2

[0135] nature VMX6100 IEx1 IEx2 Shore A Hardness 57 52 53 100% Modulus 1.4MPa 1.2MPa 1.3MPa Tensile Strength 10.7MPa 11.7MPa 10.5MPa Ultimate elongation 908% 817% 739% 25% tensile permanent deformation Invalidation 24 22.8 50% tensile permanent deformation Invalidation 48.8 46

[0136] As shown in Table 2, the experimental ABA elastomeric ionomers exhibited tensile properties and hardness values ​​comparable to the control VMX6100. However, when the elastic properties were measured by using 25% and 50% elongation at 70°C, the ionomers exhibited superior functionality.

[0137] The rheological properties of each of the experimental samples IEx1 and IEx2 and the control sample VMX6100 were evaluated using SAOS at 190°C. The results are shown in Table 3 below, and the complex viscosity is shown in Figure 2A The neutral shear modulus is shown in Figure 2B In the (vanGurp-Palmen (VGP) curve).

[0138] Table 3

[0139]

[0140]

[0141] Table 3 (continued)

[0142]

[0143] As shown in Table 3 and Figure 2A and 2B As provided in , the ABA elastomeric ionomer is comparable to the control sample and therefore exhibits appropriate rheological properties.

[0144] The properties of IEx1 were compared to several additional controls, including 100% elongation (Methods 3 and 4). Controls included VMX6100, INFUSE TM9507 (DOW CHEMICAL, Michigan, USA, olefin block copolymer), INFUSE TM 9100 (DOW CHEMICAL, Michigan, USA, olefin block copolymer) and Kraton TM G1657 (KRATON CORPORATION, Texas, USA, styrene and ethylene / butylene copolymer).

[0145] Table 4

[0146]

[0147]

[0148] As shown in Table 4, the experimental ABA elastomeric ionomers exhibit superior tensile properties compared to most control copolymers. In addition, the experimental ionomers are able to achieve excellent elastic properties (e.g., Figure 3 (shown in the middle figure) and shows no stickiness.

[0149] Example 2. In this example, six experimental KOH propylene elastomeric ionomers were prepared in accordance with the present disclosure and as described above using EXXONMOBIL VISTAMAXX TM V350 (V350) or ACTI-TECH TM 16MA13 was prepared and compared with V350 and three control samples of V350 ionomerized with zinc stearate (ZnAc).

[0150] First, the maleic acid (MA) content of each of V350 and 16MA13 was evaluated using FTIR. The MA content was calculated according to the following equation:

[0151] Ratio=(peak 1710+peak 1780+peak 1850) / film thickness (mm)

[0152] To confirm the proportion of MA monomer residues to grafted MA content, a comparison was made between pure V350 and pure 16MA13 and annealed V350 and pure 16MA13. Annealing was performed in an oven at 110°C overnight. The results are shown in Table 5 below.

[0153] Table 5

[0154]

[0155] As shown in Table 5, the MA content is relatively large in the 16MA13 sample.

[0156] Thereafter, the molecular weight distribution was determined using gel permeation chromatography as described above. Figure 4 The resulting differential molecular weight (dWf / dLogM) curves are provided in and the results are listed below in Table 6. C2% is the amount of ethylene.

[0157] Table 6

[0158]

[0159] As shown, the molecular weight as well as the ethylene content of both V350 and 16MA13 are comparable.

[0160] As described in this article, BRABENDER TM The six experimental and control samples were prepared using a mixer (60 rpm until torque stabilized) and the temperatures and concentrations in Table 7 below.

[0161] Table 7

[0162] Formula (weight %) Process conditions (℃) V350 / 1%KOH 110 V350 / 1% KOH 150 V350 / 1%KOH 200 V350 / 0.5%KOH 150 16MA13 / 1%KOH 150 16MA13 / 0.5%KOH 150 V350 (control) 150 16MA13 (control) 150 V350 / 1% ZnAc (control) 110

[0163] The rheological properties of each of the experimental and control samples were evaluated using SAOS at 190 °C. Figures 5A to 5C The complex viscosity, storage modulus and loss modulus results are shown in Figure 1. As can be seen, the V350 / 1% ZnAc control shows no ionomerization effect, as its curve is close to equal to that of V350 without the addition of ZnAc. However, the KOH samples all show ionomerization and produce deviating curves. Clearly, the KOH ionomerization with V350 is stronger than that with 16MA13. Therefore, KOH effectively ionomerizes MA-grafted propylene elastomeric polymers and exhibits higher melt viscosity and modulus at low angular frequency ranges, indicating higher melt strength.

[0164] The samples (excluding the ZnAc control sample) were evaluated for tensile strength (stress) and ultimate elongation at 190°C as described above. The results are shown in Figure 6 As shown, both the V350 and 16MA13 samples show sagging with elongation, however this is not observed on the KOH sample, indicating improved melt strength through ionomerization. In addition, it is observed that the ionomerized products from V350 show higher tensile stress and lower elongation at break than those from 16MA13.

[0165] The V350 samples were tested using DMTA as described above and the results are provided in Tables 7A to 7D. As shown, the storage modulus and loss modulus of V350 / 1% KOH processed at various temperatures showed good retention at higher temperatures compared to V350 and V350 / 1% ZnAc, indicating improved thermal stability and complex viscosity of V350 / 1% KOH at high temperatures, which would indicate improved melt strength. In addition, the tan delta value of V350 / 1% KOH is lower than that of V350 and V350 / 1% ZnAc, indicating improved elasticity.

[0166] Now refer to Figure 8 , providing the FTIR curves of the 1% KOH sample compared to the control sample. 1780cm -1 The peak at 1710 cm represents the vibration peak of C=O in MA, and the peak at 1710 cm -1 It is the symmetrical C=O stretch of maleic acid. After neutralization, the signal shifts to 1570 cm -1 , a signal of asymmetric COO-stretching. Figure 8 Shown in Figure 1, with 1% KOH added, 1710 cm in V350 -1 and 1780cm -1 The signal of 16MA13 no longer exists, while such a peak in 16MA13 shows only a very weak signal, suggesting that the MA group is completely or substantially completely neutralized.

[0167] T of 1% KOH (150℃) sample compared with control sample c , T m and ΔH. The results are shown in Table 8 below.

[0168] Table 8

[0169] formula Tc(℃) Tm(℃) ΔH(J / g) V350 56.9 64.8,145.6 9.0 V350 / 1%KOH, 150℃ 73.4 119.4 6.3 V350 / 1% ZnAc, 150℃ 69.7 115.7 7.7

[0170] With the addition of KOH or ZnAc, the control V350 had T values ​​of 64.8 and 145.6 °C. m The double peaks of V350 were changed to a single peak at about 115-120° C. The peak crystallization temperature was increased compared to the control V350, while the heat of crystallization did not change significantly, indicating that the crystallinity was essentially unchanged.

[0171] Compression set measurements (70°C, 22 hours, 25% deformation) were performed as described above. The results are shown in Fig. 9 As shown, each of the 1% KOH experimental samples improved by approximately 15% compared to the control V350 sample, indicating a higher elasticity of the ionomer product compared to V350. The results are consistent with the DMTA results.

[0172] The tensile strength was measured at room temperature and a tensile speed of 100 mm / min. Each of the KOH samples was treated at 150°C. The results are shown in Fig. 10A and 10B The elongation (elastic recovery) was measured at 1 mm / s and the KOH samples were each treated at 150°C. The results are shown in Fig.11A and 11B The tensile strength at break, elongation at break, tensile set and hysteresis values ​​are provided in Table 9 below.

[0173] Table 9

[0174]

[0175] As shown, all KOH samples exhibited elongation at break greater than 900%, indicating good stretchability of the ionomers. In addition, tensile strength was increased in the KOH samples compared to the control.

[0176] Therefore, the present invention is well suited to obtain the results and advantages mentioned and inherent therein. The specific embodiments and configurations disclosed above are illustrative only, because it is obvious that different but equivalent means can be adopted to modify and implement the present invention for those skilled in the art who benefit from the teachings herein. In addition, except as described in the following claims, it is not intended to limit the details of the configuration or design shown herein. It is therefore obvious that the specific illustrative embodiments disclosed above can be changed, combined or modified, and all such changes are considered to be within the scope and spirit of the present invention. In the absence of any element not specifically disclosed herein and / or any optional element disclosed herein, the invention disclosed illustratively herein can be appropriately implemented. Although compositions and methods are described in terms of "comprising", "containing" or "including" various components or steps, the compositions and methods can also be "essentially composed of various components and steps" or "composed of various components and steps". All numerical values ​​and ranges disclosed above can be changed to a certain extent. Whenever a numerical range with a lower limit and an upper limit is disclosed, any numerical value and any included range falling within the range are specifically disclosed. In particular, each range of values ​​disclosed herein (having the following format "from about a to about b", or equivalently "from about a to b", or equivalently "from about ab") should be understood to recite each value and range contained within the broader range of values. Likewise, the terms in the claims have their ordinary, general meaning unless otherwise explicitly and clearly defined by the patentee. In addition, the indefinite articles "a" or "an" as used in the claims are defined herein to mean one or more than one of the element it introduces.

Claims

1. A functionalized polyolefin elastomer ionomer composition comprising: The reaction product of: Polyolefin components; at least 0.1 parts by weight of a sulfonyl azide derivative component, the sulfonyl azide derivative component functionalizing the polyolefin component, wherein the sulfonyl azide derivative component comprises at least one of an organic anhydride compound or an organic acid compound, and wherein the sulfonyl azide derivative component is present in a certain amount per 100 parts by weight of the polyolefin component; and a metal-based neutralizer component containing an elemental metal or metal compound comprising at least one of aluminum, calcium, magnesium, sodium and zinc, The degree of neutralization of one or both of the organic anhydride component and the organic acid component of the sulfonyl azide derivative component is at least 20%.

2. The functionalized polyolefin elastomeric ionomer composition of claim 1, wherein the polyolefin component is a propylene-ethylene copolymer.

3. The functionalized polyolefin elastomer ionomer composition of claim 1, wherein the sulfonyl azide derivative component is selected from the group consisting of 4-carboxybenzenesulfonyl azide (CBSA), 3-azidosulfonylbenzoic acid, 5-(azidosulfonyl)endo-cis-bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, 3-(2,5-dioxotetrahydrofuran-3-yl)-2-methylpropane-1-sulfonyl azide, and any combination thereof.

4. The functionalized polyolefin elastomeric ionomer composition of claim 1, wherein the metal based neutralizer compound is a carboxylated copolymer of a calcium carboxylate or a zinc carboxylate based on an acid compound selected from linear and branched monocarboxylic acids having at least 12 carbon atoms per molecule.

5. The functionalized polyolefin elastomer ionomer composition of claim 1 wherein the metal based neutralizer compound is a zinc carboxylate based on a linear monocarboxylic fatty acid having at least 12 carbon atoms per molecule.

6. The functionalized polyolefin elastomer ionomer composition of claim 1, wherein the metal-based neutralizing agent is a metal hydroxide or metal oxide of at least one of aluminum, calcium, magnesium, sodium, and zinc.

7. The functionalized polyolefin elastomer ionomer composition of claim 1, wherein the metal-based neutralizing agent is calcium stearate or zinc stearate.

8. Methods, including: Melt Mixing: Polyolefin components; at least 0.1 parts by weight of a sulfonyl azide derivative component, the sulfonyl azide derivative component functionalizing the polyolefin component, wherein the sulfonyl azide derivative component comprises at least one of an organic anhydride compound or an organic acid compound, and wherein the sulfonyl azide derivative component is present in a certain amount per 100 parts by weight of the polyolefin component; and a metal-based neutralizer component containing an elemental metal or metal compound comprising at least one of aluminum, calcium, magnesium, sodium and zinc, The degree of neutralization of one or both of the organic anhydride component and the organic acid component of the sulfonyl azide derivative component is at least 20%.

9. The method according to claim 8, wherein the melt mixing is carried out using a reactor or an extruder.

10. The method of claim 8, wherein the melt mixing is performed at a temperature of about 100°C to about 200°C.

11. The method of claim 8, wherein the polyolefin component is a propylene-ethylene copolymer.

12. The method of claim 8, wherein the sulfonyl azide derivative component is selected from 4-carboxybenzenesulfonyl azide (CBSA), 3-azidosulfonylbenzoic acid, 5-(azidosulfonyl)endo-cis-bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, 3-(2,5-dioxotetrahydrofuran-3-yl)-2-methylpropane-1-sulfonyl azide, and any combination thereof.

13. The method of claim 8, wherein the metal-based neutralizer compound is a carboxylated copolymer of a calcium or zinc carboxylate based on an acid compound selected from linear and branched monocarboxylic acids having at least 12 carbon atoms per molecule.

14. The method of claim 8, wherein the metal-based neutralizer compound is a zinc carboxylate based on a linear monocarboxylic fatty acid having at least 12 carbon atoms per molecule.

15. The method of claim 8, wherein the metal-based neutralizing agent is a metal hydroxide or metal oxide of at least one of aluminum, calcium, magnesium, sodium, and zinc.

16. The method of claim 8, wherein the metal-based neutralizing agent is calcium stearate or zinc stearate.

17. The carboxypropylene elastomer ionomer composition comprises: The reaction product of: a polyolefin component grafted with anhydride; and A metal hydroxide based neutralizer component contains an elemental metal or metal compound comprising at least one of potassium, sodium or calcium.

18. The carboxylated propylene elastomeric ionomer according to claim 17, wherein the acid anhydride is maleic anhydride or succinic anhydride.

19. The carboxylated propylene elastomeric ionomer of claim 17, wherein the metal hydroxide based neutralizing agent is potassium hydroxide.

20. The carboxylated propylene elastomeric ionomer of claim 17, wherein the polyolefin component is a propylene-ethylene copolymer.